Passive Damper Network in a Simple DC Distribution Power System - Awang Bin Jusoh; Muhammad Firdaus Abd Razak; Mohamad Hamka Bin Saiful; Tole Sutikno (Institute of Advanced Engineering and Science, 2018)
Distributed power system (DPS) distributes power amongst processing units such as power electronics converters with DC system. Due to the increasing usage of power converters in DPS system, the system becomes unstable and the converter tends to draw constant power needed by the load of the system. Constant power load (CPL) characteristic has negative input impedance that could produce instability problems in the DC bus system. Passive damping network which consists of series RC damping circuit was connected in parallel to the DC bus system with the purpose to reduce the instability. The passive damper was designed, simulated with MATLAB/Simulink and verified experimentally with different values of CPL power levels and input voltage changes. The obtained simulation results show that simple DC system with constant power load was successfully stabilized by the installation of the passive damping network. The experimental set up was also conducted to validate of the proposed technique, and the obtained results were in excellent agreement with the theoretical parts of the project.